1997
DOI: 10.1002/(sici)1096-9063(199701)49:1<76::aid-ps491>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the New Herbicide KIH-6127. Part III. Synthesis and Structure-Activity Studies of Analogues of KIH-6127 against Barnyard Grass (Echinochloa oryzicola)*

Abstract: The previously evaluated prototype, methyl 6‐acetyl‐2‐[(4,6‐dimethoxypyrimidin‐2‐yl)oxy]benzoate, was modified by the introduction of an oximino group. Further extensive synthetic modifications were then made to the 6‐alkyl moiety (R1), the ester moiety (R2), the alkoxyimino moiety (R3), the bridge‐atom (X) and the 4,6‐disubstituted‐pyrimidine moiety (A, B, Z). Structure–activity relationships of the synthesized compounds were studied by examining their herbicidal activity against Barnyard grass (Echinochloa o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…in 1996 (Tokyo, Japan;Tamaru and Saito, 1996). Tamaru et al (1997) reported that (E), isomer (I), has been confirmed to restrain the plant enzyme acetolactate synthase (ALS) and prevent branched chain amino acid biosynthesis, and the (E), or pyriminobac-methyl (EPM), showed stronger soil adsorption and weaker hydrophilic properties than (Z), or pyriminobac-methyl (ZPM); thus, EPM was selected as the best compound to develop a commercial weedicide, which is commonly used to control the growth of sedges and both gramineous and annual weeds. The chemistry of EPM is well understood; the octanol-water partition coefficient is 2.31 (low) at pH 7 and 20 • C, the solubility in the water is 9.25 mg L −1 (low) at 20 • C, and the vapor pressure is just 3.1 × 10 −5 Pa (low) at 20 • C (Lewis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…in 1996 (Tokyo, Japan;Tamaru and Saito, 1996). Tamaru et al (1997) reported that (E), isomer (I), has been confirmed to restrain the plant enzyme acetolactate synthase (ALS) and prevent branched chain amino acid biosynthesis, and the (E), or pyriminobac-methyl (EPM), showed stronger soil adsorption and weaker hydrophilic properties than (Z), or pyriminobac-methyl (ZPM); thus, EPM was selected as the best compound to develop a commercial weedicide, which is commonly used to control the growth of sedges and both gramineous and annual weeds. The chemistry of EPM is well understood; the octanol-water partition coefficient is 2.31 (low) at pH 7 and 20 • C, the solubility in the water is 9.25 mg L −1 (low) at 20 • C, and the vapor pressure is just 3.1 × 10 −5 Pa (low) at 20 • C (Lewis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In 1996 (Tokyo, Japan) (Tamaru and Saito 1996). Tamaru et al (1997)) reported that (E) -isomer (I) has been confirmed to restrain the plant enzyme acetolactate synthase (ALS) and prevent branched chain amino acid biosynthesis, and the (E) -pyriminobac-methyl (EPM) showed stronger soil adsorption and weaker hydrophilic properties than (Z) -pyriminobac-methyl (ZPM), thus EPM was selected as the best compound to develop a commercial weedicide, which is commonly used to control the growth of sedges and both gramineous and annual weeds.…”
Section: Introductionmentioning
confidence: 99%